2021
DOI: 10.1039/d1ta04821j
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of structural order in bipolar redox-active molecules for organic redox flow batteries

Abstract: Bipolar redox-active molecules (BRMs) have been suggested as a means to address crossover related issues in all-organic redox flow batteries (RFBs). In such species, electron donors (anolytes) and electron acceptors...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The simple hybrid design with moderate polarity was soluble up to 0.3 M in 1,3-dioxolane with 1.0 M TBABF 4 and showed good chemical stability over 50 cycles with current densities ranging from 20 to 60 µA cm −2 (1.0 to 3.0 C). However, although small molecules and short linkers could instinctively reduce the need for solubilizing molecular parts that do not partake in the charging or discharging process, Li et al showed important irregularities in chemical behavior between phenothiazine and phthalimide moieties tethered through various chain length linkers [161]. Molecular conformations arising from specific chain lengths and flexibilities are found to have a profound effect on the ability to undergo charge transfer and the molecular packing.…”
Section: Bipolar Electrolytesmentioning
confidence: 99%
“…The simple hybrid design with moderate polarity was soluble up to 0.3 M in 1,3-dioxolane with 1.0 M TBABF 4 and showed good chemical stability over 50 cycles with current densities ranging from 20 to 60 µA cm −2 (1.0 to 3.0 C). However, although small molecules and short linkers could instinctively reduce the need for solubilizing molecular parts that do not partake in the charging or discharging process, Li et al showed important irregularities in chemical behavior between phenothiazine and phthalimide moieties tethered through various chain length linkers [161]. Molecular conformations arising from specific chain lengths and flexibilities are found to have a profound effect on the ability to undergo charge transfer and the molecular packing.…”
Section: Bipolar Electrolytesmentioning
confidence: 99%
“…A specific approach involves connection of two independent electronically decoupled redox-active cores with an inert linker. Even though such a strategy can provide modularity in bipolar electrolyte design, it can significantly inflate the molecular weight, in addition to introducing nontrivial and potentially detrimental effects of the linker structure on stability . A more challenging approach that could address these limitations involves introducing two electrophores into a single π-system. ,, Although conjugation of two redox orthogonal functionalities increases peak-to-peak separation between redox events, it leads to destabilization of both charged states.…”
Section: Introductionmentioning
confidence: 99%
“…Similar symmetric cell architectures have been explored in the development of bipolar organic molecules, though they have yet to be commercialized. [29][30][31][32][33][34] To address the inherent tradeoff relationship between the solute concentration and the performance of RFBs, we are interested in designing a rechargeable half-cell reaction where the charged and discharged species are both gaseous. With this approach, the redox-active gas, in principle, no longer needs to remain dissolved in the electrolyte all the time and can be stored in a gas tank and supplied on demand (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%